Individuality vs individualism: balancing personal freedom and social responsibility - Mushtaq, Hira; Mughal, Muhammad Junaid; Chisti, Siddiq Ali (THE LEARNING RESEARCH & EDUCATIONAL CURVE, 2025)
In contemporary discourse on human behavior and society, the concepts of individuality and individualism have gained considerable attention. While individuality denotes the unique traits, talents, and perspectives that define a person, individualism a philosophy rooted in Western thought prioritizes personal freedom, autonomy, and self-interest, sometimes at the expense of collective welfare. Exploring these concepts is crucial for understanding the interplay between personal growth and social responsibility. This study employs a qualitative approach, analyzing Qur’anic verses, Prophetic ?ad?th, and scholarly interpretations to examine how Islamic thought harmonizes individuality with communal well-being. Key concepts such as nafs (self), Ummah (community), Tarbiyyah (personal development), and Ta?l?m (education) highlight a framework where personal development is ethically guided and socially responsible. Islamic teachings encourage self-discipline, moderation, respect for family, pursuit of knowledge for societal benefit, and prioritization of collective welfare. Findings reveal that, unlike Western individualism, which often emphasizes self-centered autonomy, Islam integrates individual growth with ethical accountability and social cohesion. The study concludes that the Islamic model provides a balanced pathway, enabling individuals to flourish personally while actively contributing to the moral, social, and spiritual advancement of society